The traits of fresh and frozen semen on brahman bulls - Triva Murtina Lubis; Prabowo Purwono Putro; Aris Junaidi; Sumarti Suryaningsih (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
The present study aimed to determine quality and parameters traits of both fresh and frozen semen in 4-year old Brahman bulls. Semen was collected from 5 bulls twice a week using artificial vagina in Ungaran ArtificialInsemination Center, Central Java, Indonesia. Immediately after collection, samples were evaluated for semen volume, color, odor, viscosity, mass movement, individual movement, spermatozoa concentration and livespermatozoa percentage. Sperm concentration was measured using a spectrophotometer. Good quality fresh semen was processed to be frozen semen. Parameters evaluated for frozen semen include spermatozoa individualmovement, live spermatozoa, and abnormal spermatozoa percentage. The results showed that the semen volume is 6.90 ± 0.54 whereas the average of sperm concentration, individual motility and live sperm are 1754.54 ± 212.67;65.50 ± 3.74% and 76.30 ± 2.64%, respectively. Meanwhile, for frozen semen, the average percentage of motility is 38.00 ± 2.74% while the average proportions of live sperm and abnormal sperm are respectively 45.20 ± 9.86% and 6.00 ± 2.83%. In conclusion, in average, all parameters of fresh and frozen semen of Brahman bulls are in normal range. Based on the Indonesian National Standard, frozen semen produced could be used for insemination